2015
DOI: 10.12659/msm.892712
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hybrid Constructs with 2-Level Artificial Disc Replacement and 2-Level Anterior Cervical Discectomy and Fusion for Surgical Reconstruction of the Cervical Spine: A Kinematic Study in Whole Cadavers

Abstract: BackgroundMulti-level cervical degeneration of the spine is a common clinical pathology that is often repaired by anterior cervical discectomy and fusion (ACDF).The aim of this study was to investigate the kinematics of the cervical spine after hybrid surgery compared with 2-level ACDF.Material/MethodsFive freshly frozen, unembalmed whole human cadavers were used including 3 males and 2 females with a mean age of 51±8 years. After evaluating the intact spine for range of motion (ROM), sagittal alignment and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…In the present study, adjacent segment disease was not compared between the modified laminoplasty and combined anterior-posterior approaches due to a short follow-up period. Although the motion-sparing nature of laminoplasty may be protective against adjacent segment disease [ 13 ], the non-fusion strategy of anterior approach, such as artificial disc replacement and hybrid surgery, could also increase adjacent motion [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, adjacent segment disease was not compared between the modified laminoplasty and combined anterior-posterior approaches due to a short follow-up period. Although the motion-sparing nature of laminoplasty may be protective against adjacent segment disease [ 13 ], the non-fusion strategy of anterior approach, such as artificial disc replacement and hybrid surgery, could also increase adjacent motion [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Faizan et al [ 24 ] revealed that the spinal stiffness after HS was far closer to intact construct in all bending motions except extension, compared to 2-level fusion. Liu et al [ 25 ] showed that 2-level hybrid surgery and ACDR did not alter ROM and minimally changed ICR at the adjacent levels compared to 2-level fusion. For 3-level cervical surgery, Ding et al [ 26 ] stated that HS may be a rational alternative to ACDF for 3-level cervical disease due to the equivalent or improved early clinical outcomes, with less impact at adjacent levels.…”
Section: Discussionmentioning
confidence: 99%
“…33 The instantaneous center of rotation (ICR) is a measure used to detect abnormal cervical spine mobility. A recent biomechanical analysis on full cadaveric specimens by Liu et al 34 showed that both hybrid surgery and CDA in 2-level reconstructions did not alter ROM and minimally changed the ICR at levels adjacent to the construct when compared with fusion alone. Both the hybrid and CDA constructs preserved not only quantitative motion but also qualitative motion by maintaining a near native ICR.…”
mentioning
confidence: 99%
“…Both the hybrid and CDA constructs preserved not only quantitative motion but also qualitative motion by maintaining a near native ICR. 34 There still remains a lack of high-quality evidence in favor of arthroplasty, ACDF, or HS for the treatment of multilevel DDD.…”
mentioning
confidence: 99%
See 1 more Smart Citation